O controle dos atos de concentração: aspectos jurídicos e econômicos - Araújo, Daniel de Oliveira (2014)
The subject of this paper is to analyze the conditions which approving or rejection of acts of economic concentration in the context of merger control applied by CADE, the paper's approach is from economic and legal perspectives. The problem is framed in the restructuring of the Brazilian state and the national economy resulting from the set of important transformations that Brazilian society experienced during the 80s and 90s of the twentieth century process. In this direction, the Federal Constitution of 1988 instituted an economic order predicated upon the principles of market economy, in which state intervention is mostly limited to regulation of economic activities and the private sector plays an important role in driving the economy and development of Brazil. This framework promoted the growth of the importance of antitrust law in the country, as it its aim is to preserve market mechanisms. And, to complete the proposed analysis, this paper describes and evaluates the economic organization established by the Constitution and presents the Brazilian System for Protection of Competition, under Brazilian antitrust law. It exposes economic theory to the examination of mergers under the law of competition. Also, analyzes the regulatory provisions contained in Law 12,529 / 2011 regulating the mergers control. This law repealed Law 8884/94 and restructured the Brazilian System for Protection of Competition - BSPC. The Law 12,529 / 2011 introduced several changes in the legal discipline of mergers to streamline the institutional structure of the competent bodies for the prevention and repression of anticompetitive conduct, it aims to increase efficiency and it changed the processes and control parameters of concentration economic – it states that mergers only become legally effective by CADE’s approval.